Pemikiran Ibnu Khaldun Tentang filsafat Pendidikan Islam - Rizki Kurniawan; Riswan Riswan; Sulaeman Abdul Azis; Herdi Herdi; Yurna Yurna (Pusat Riset dan Inovasi Nasional, 2023)
Ibn Khaldun's thoughts on the philosophy of Islamic education reflect his valuable contribution in understanding the role of education in the formation and advancement of civilization. In his famous work,